2023
DOI: 10.1287/mnsc.2022.4655
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dispute Resolution in Two-Sided Platforms: The Case of Review Blackmail

Abstract: We study the relative merits of different dispute resolution mechanisms in two-sided platforms in the context of disputes involving malicious reviews and blackmail. We develop a game-theoretic model of the strategic interactions between a seller and a (potentially malicious) consumer. In our model, the seller takes into account the impact of consumer reviews on his future earnings; recognizing this, a malicious consumer may attempt to blackmail the seller by purchasing the product, posting a negative review, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…They showed that in a two-sided market, two platforms of different sizes can coexist under the influence of negative group endogeneity, even though the larger platform is more efficient. Papanastasiou et al [31] argued that negative consumer ratings affect the platform's future revenues. If companies can delete reviews on their own and penalize violations, this can effectively mitigate the negative impact on the platform.…”
Section: 3mentioning
confidence: 99%
“…They showed that in a two-sided market, two platforms of different sizes can coexist under the influence of negative group endogeneity, even though the larger platform is more efficient. Papanastasiou et al [31] argued that negative consumer ratings affect the platform's future revenues. If companies can delete reviews on their own and penalize violations, this can effectively mitigate the negative impact on the platform.…”
Section: 3mentioning
confidence: 99%